COVID-19 INFECTION PREVENTION AND CONTROL IN AN OIL AND GAS COMPANY - Sony Dwi Risvandi; Fatma Lestari (Journal of Industrial Hygiene and Occupational Health, 2021)
Coronavirus Disease 2019 (Covid-19) is a respiratory disease that spread around the world and has been declared as a Public Health Emergency of International Concern (PHEIC) by the World Health Organization (WHO). Covid-19, which has been declared as an international pandemic, has not only impacted public health but also business operations and the safety of workers in the workplace. Despite such circumstances, several vital businesses still operate due to its necessity status. One of such industries that continue to operate during the Covid-19 pandemic is the oil and gas industry. The purpose of this paper is to provide an overview of the implementation of Covid-19 prevention and control in the workplace of PT. X, a company which works on said sector. This study uses a Qualitative approach to collect data through key personnel interviews. This is then supported by observations of company policies; procedures; health surveillance; and the testing, detection, and tracking protocol. Covid-19 Pandemic Preparedness Procedure developed by PT. X was intended to mitigate this specific situation. This procedure covers various aspects such as employee work arrangements; self-assessment for early detection; health protocols; health surveillance; information, education, and communication to all employees. Data has shown that during this pandemic, PT. X’s safety performance indicators, i.e., Lost Time Injury Frequency and Total Recordable Injury Rate, is still below the acceptable criteria set by the company. This study finds that Covid-19 prevention and control policy by PT. X has properly followed the relevant health, industry, and labor regulations in Indonesia. PT. X has implemented a risk assessment in its operation during the pandemic to maintain business continuity while controlling the risk of Covid-19 transmission. The findings of the study highlighted the application of health protocols, drivers, obstacles, and challenges that are common in the oil and gas industry.